In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be

x + 3 = 48 => x = 45
or
(x + 1) = 48 => x = 47
However, at least one of these solutions fails to work when substituted back into the original equation. Why is that? Please help Eric to understand better; solve the problem yourself, and explain your reasoning.

Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. Eric is solving the inequality 9x + 15 ≥51 and graphing the solution. Which of the following describe the steps he should take
    1. answers icon 1 answer
more similar questions